Herpes zoster ophthalmicus: a medical review. Issue 8 (August 1981) - Lightman, S.; Marsh, R. J.; Powell, D.
Abstract : Patients with herpes zoster undergo extensive screening to detect underlying malignant disease which is compromising their immunity. In a retrospective survey of 1000 patients with herpes zoster ophthalmicus 12 patients had malignant disease which was known on presentation. No new cases were detected or discovered on follow-up. Three patients developed a disseminated rash, but none of these had an underlying malignant disease.